The A list : an Ali Reynolds mystery - Jance, Judith A (Jance, Judith A. Ali Reynolds mysteries., 2019)
The death of an old friend brings Ali back to the last story she ever reported: a feel-good human interest piece about a young man in need of a kidney to save his life, which quickly spiraled into a medical mismanagement scandal that landed a prestigious local doctor in prison for murder. Years may have passed, but Dr. Edward Gilchrist has not forgotten those responsible for his downfall<U+2014>certainly not Ali Reynolds, who exposed his dirty deeds to the world. Life without parole won<U+2019>t stop him from getting his revenge. Tattooed on his arm are the initials of those who put him behind bars, and he won<U+2019>t stop until every person on that Annihilation List is dead.